The structure of the banking sector, credit screening and firm risk - Tröge, Michael (online, 1999)
Abstract:
urn:nbn:de:0168-ssoar-194793
Keywords: (stw)Bank; (stw)Wettbewerb; (stw)Kreditwürdigkeit; (stw)Auktionstheorie; (stw)Informationsverhalten; (stw)Industrieökonomik; (stw)Wohlfahrtsanalyse; (stw)Theorie; (thesoz)Oligopol; (thesoz)Kreditvergabe; (thesoz)ökonomisches Modell; (thesoz)Marktform; (thesoz)Bankgewerbe; (thesoz)Risiko; (thesoz)Markt; (thesoz)Wettbewerb; (thesoz)Information; (thesoz)Kosten; (thesoz)Unternehmen; (thesoz)Struktur; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Bank; Wettbewerb; Kreditwürdigkeit; Auktionstheorie; Informationsverhalten; Industrieökonomie; Wohlfahrtseffekt; Theorie